Loss of tenomodulin expression is a risk factor for age‐related intervertebral disc degeneration. Issue 3 (21st February 2020) - Lin, Dasheng; Alberton, Paolo; Delgado Caceres, Manuel; Prein, Carina; Clausen‐Schaumann, Hauke; Dong, Jian; Aszodi, Attila; Shukunami, Chisa; Iatridis, James C; Docheva, Denitsa
Abstract: The intervertebral disc (IVD) degeneration is thought to be closely related to ingrowth of new blood vessels. However, the impact of anti‐angiogenic factors in the maintenance of IVD avascularity remains unknown. Tenomodulin ( Tnmd ) is a tendon/ligament‐specific marker and anti‐angiogenic factor with abundant expression in the IVD. It is still unclear whether Tnmd contributes to the maintenance of IVD homeostasis, acting to inhibit vascular ingrowth into this normally avascular tissue. Herein, we investigated whether IVD degeneration could be induced spontaneously by the absence of Tnmd . Our results showed that Tnmd was expressed in an age‐dependent manner primarily in the outer annulus fibrous (OAF) and it was downregulated at 6 months of age corresponding to the early IVD degeneration stage in mice. Tnmd knockout ( Tnmd − / − ) mice exhibited more rapid progression of age‐related IVD degeneration. These signs include smaller collagen fibril diameter, markedly lower compressive stiffness, reduced multiple IVD‐ and tendon/ligament‐related gene expression, induced angiogenesis, and macrophage infiltration in OAF, as well as more hypertrophic‐like chondrocytes in the nucleus pulposus. In addition, Tnmd and chondromodulin I ( Chm1, the only homologous gene to Tnmd ) double knockout ( Tnmd − / − Chm1 − / − ) mice displayed not only accelerated IVD degeneration, but also ectopic bone formation of IVD. Lastly, the absence of Tnmd in OAF‐derived cells promoted p65 and matrix metalloproteinases upregulation, and increased migratory capacity of human umbilical vein endothelial cells. In sum, our data provide clear evidences that Tnmd acts as an angiogenic inhibitor in the IVD homeostasis and protects against age‐related IVD degeneration. Targeting Tnmd may represent a novel therapeutic strategy for attenuating age‐related IVD degeneration. Abstract : Cartoon highlighting the hallmarks of Tnmd −/− intervertebral disc (IVD) phenotype. Tnmd −/− mice exhibited more rapid progression of age‐related IVD degeneration. These signs include lower disc height index, smaller collagen fibrils with lower compressive stiffness in the outer annulus fibrosus, reduced multiple IVD‐ and tendon/ligament‐related gene expression, induced angiogenesis and macrophage infiltration in outer annulus fibrous, as well as more hypertrophic‐like chondrocytes in the nucleus pulposus.